Cultura organizacional y autopercepción del desempeño docente en las instituciones educativas del nivel primaria Red N° 7 Callao - Morocho Cáceres, Ana Cecilia (2012)
This research present aims correlation description to relate the educational organizational culture and teaching performance of primary level educational institutions belongs to seven red of Callao. The sample consisted of 184 teachers. The instruments were used a questionnaire of Education Organizational Culture Inventory Marcone (2003) and questionnaire of teaching performance on the Valdés (2000) approach were used. The results show that there is significant correlation between organizational culture and teaching performance. Nevertheless there is prevalence medium levels of teaching performance. It was concluded that the organizational culture of education is an effective tool for teacher performance.